Commissioner Diversity, Environmental Pressures, and Sustainability Disclosure Before and During The COVID-19 Pandemic - Muhammad Wisnu Girindratama; Nurma Juwita; Setyaningtyas Honggowati; Doddy Setiawan (Universitas Pendidikan Ganesha, 2024)
This study aims to examine the influence of the diversity of the board of commissioners and environmental pressures on the disclosure of sustainability reports before and during the COVID-19 pandemic. This research is quantitative and uses secondary data obtained from annual reports and sustainability reports issued by each company. The sample was determined using a purposive sampling technique. Before the COVID-19 pandemic, the size of the board of commissioners had a negative effect on the disclosure of sustainability reports, while gender, education, and citizenship diversity had a positive effect. During the COVID-19 pandemic, gender diversity and the size of the board of commissioners positively affected the disclosure of sustainability reports, whereas education and citizenship diversity had no effect. This study compares the influence of the diversity of the board of commissioners and environmental pressures before and during the COVID-19 pandemic.